Fostering innovation through creativity stimulation methods in Croatia - Valerija Botrić; Ljiljana Božić (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Purpose - The key question addressed in the paper is whether creativity fostering methods increase innovation output in Croatian firms. Design/methodology/approach - By utilizing the Community Innovation Survey 2010 data and propensity score matching methods, we estimate the average treatment effect of the treated (i.e. firms that employ creativity stimulation methods). Within this framework, our measured outcome is the innovation activity of the firm and the treatment is the creativity stimulation method used by the firm. Findings - The results confirm that the creativity enhancing methods have a positive impact on innovation activity in Croatian enterprises. The empirical analysis of average treatment effect of the treated reveals that the most effective measure seems to be training, followed closely by multidisciplinary working teams. Non-financial creativity enhancing methods seem to be least effective. Research limitations/implications - The results follow some stylized facts related to Croatian enterprises. However, since this paper provides first attempt of the analysis of these issues, future research efforts are required to substantiate our findings. Originality/value - The analysis of effectiveness of creativity fostering methods for innovation activity has proved that the innovation activity can be enhanced by employing each of the method analysed in the paper.
Keywords: O31; 330; creativity; innovation; Croatia